The impact of environmental uncertainty on the performance of the rice supply chain in the Ayeyarwaddy Region, Myanmar - Thuzar Linn; Broos Maenhout (Agricultural and Food Economics, 2019)
In this paper, we study the relationship between environmental uncertainty and performance in the rice supply chain in the Ayeyarwaddy Region, Myanmar. Efficiency is one of the important performance indicators in both supply chain and agribusiness. In this regard, the objectives of the study are to identify the different sources of uncertainty perceived by the different actors in the supply chain, to measure the rice supply chain efficiency, and to study the impact of the environmental uncertainty on the supply chain efficiency. The data of 215 respondents is collected from the Ayeyarwaddy Region by using a purposive and stratified random sampling method, and we analyze this data via descriptive statistics, an exploratory factor analysis, data envelopment analysis (DEA), and Tobit regression analysis. The scores for the technical, pure, and scale efficiency show a very low performance of the rice supply chain in the Ayeyarwaddy Region resulting from the fact that most of the rice businesses are too small and need to expand their operating size. We found that this global rice supply chain performance is significantly impacted by the planning and control uncertainty and the climate uncertainty. Therefore, mitigation initiatives must be developed such as financial insurance mechanisms and extension services should be widespread. Both aim to improve the impact of the climate adverse conditions and to increase the efficiency of resource utilization in the supply chain. Moreover, the actors should organize themselves in cooperatives such that the scale of operations can be increased and information is captured and shared between different parties in the supply chain. This is crucial to operational control and planning because a higher quality of information input will increase the quality of managerial decision making.
Keywords: 330; Environmental uncertainty; Efficiency performance; Rice supply chain; Myanmar